Efficient RhB degradation and inactivation of S. aureus with molecular docking studies of PVP and GO assisted BaO nanorods - Aziz, Hamza; Imran, Muhammad; Haider, Ali; Shahzadi, Anum; Mustajab, Muhammad; Ul-Hamid, Anwar; Ullah, Hameed [UNESP]; Hussain, Ayesha; Abd-Rabboh, Hisham S.M.; Ikram, Muhammad (Elsevier, 2025)
Coprecipitation method was used to synthesize BaO and (2 and 4 wt%) of GO/PVP doped BaO nanorods (NRs) as potential catalysts for wastewater treatment. This research aims to enhance porosity, and surface area through surface functionalized GO/PVP doped NRs for antimicrobial potential and degradation of rhodamine B (RhB). Efficient RhB degradation was observed in an acidic medium (95.52 %) using sodium borohydride (NaBH4) in absence of light. The agar well diffusion method was used to investigate antimicrobial effectiveness by measuring inhibition zones at high (8.45 ± 0.04 mm) and low (7.05 ± 0.04 mm) concentrations. Molecular docking analysis was performed to establish a theoretical basis for bactericidal effects of BaO, PVP doped BaO, and GO/PVP doped BaO NRs against deoxyribonucleic acid (DNA) gyrase in S. aureus. Docking investigations demonstrate that these doped NRs showed the potential as inhibitors of DNA gyrase.
Keywords: Barium oxide; Nanorods; Porosity; RhB degradation; S. aureus; Surface area